A Hyperactive Transposase Promotes Persistent Gene Transfer of a piggyBac DNA Transposon - Erin R Burnight; Janice M Staber; Pavel Korsakov; Xianghong Li; Benjamin T Brett; Todd E Scheetz; Nancy L Craig; Paul B McCray, Jr (Elsevier, 2012)
Nonviral vector systems are used increasingly in gene targeting and gene transfer applications. The piggyBac transposon represents an alternative integrating vector for in vivo gene transfer. We hypothesized that this system could achieve persistent gene transfer to the liver when administered systemically. We report that a novel hyperactive transposase generated higher transposition efficiency than a codon-optimized transposase in a human liver cell line. Hyperactive transposase-mediated reporter gene expression persisted at levels twice that of codon-optimized transposase in the livers of mice for the 6-month study. Of note, expression persisted in mice following partial hepatectomy, consistent with expression from an integrated transgene. We also used the hyperactive transposase to deliver the human α1-antitrypsin gene and achieved stable expression in serum. To determine the integration pattern of insertions, we performed large-scale mapping in human cells and recovered 60,685 unique hyperactive transposase-mediated insertions. We found that a hyperactive piggyBac transposase conferred an altered pattern of integration from that of insect piggyBac transposase, with a decreased frequency of integration near transcription start sites than previously reported. Our results support that the piggyBac transposon combined with the hyperactive transposase is an efficient integrating vector system for in vitro and in vivo applications.